#stayhomefree - Blagojević, Jelisaveta (Identities: Journal for Politics, Gender and Culture, 2020)
Author(s): Jelisaveta Blagojević Title (English): #stayhomefree Journal Reference: Identities: Journal for Politics, Gender and Culture Publisher: Institute of Social Sciences and Humanities - Skopje Page Range: 18-19 Page Count: 2 Citation (English): Jelisaveta Blagojević, “#stayhomefree,” Identities: Journal for Politics, Gender and Culture, Vol. 17, No. 1 (Summer 2020): 18-19.